Knowledge Translation, a Challenge in Nursing Practice in the 21st Century - Tanko Titus AUTA (Humanistic Network for Science and Technology (HNST), 2019)
Health care systems are experiencing challenges of improving the quality of care and decreasing the risk of adverse events health consumers are likely to be exposed to globally. Nursing, as a social and humanistic discipline is structured within the care process, is interrelated with the phenomena of the experienced world in which the other cohabits. As the profession expands it body of knowledge based on elements from nursing practices, it has to develop instruments that qualify its care process, such as classifications that seek to diagnose, foresee results and define interventions in the health and disease process. Research has shown that proven effective intervention now exist that would enable all countries to meet the health care challenges through improvement in evidence based practice as a result of the introduction of knowledge translation in the health sector. It is believed that studies on knowledge translation are absorbed in practice, but more robust designs are needed to put these results into practice, with consequent benefits for health teams, patients and family members. Care is however required to avoid the knowledge translation imperative that would give a translational perspective to nursing research.